UPAYA PEMERINTAH ISLANDIA DALAM MENINGKATKAN KESETARAAN GENDER (STUDI KASUS : FENOMENA GENDER PAY GAP DI DUNIA KERJA) - Arlina Alfiani Chandra; Y.A. Wahyuddin; Kurnia Zulhandayani Rizki (The Department of International Relations Universitas Mataram, 2023)
This study describes the Gender pay gap in Iceland and the government's efforts to eliminate the Gender pay gap in the world of work. The purpose of this research is to find out what actions are taken by the government to improve gender equality through public policies. This study used qualitative research methods. Data collection was obtained through literature study sourced from books, journals, articles, government documents, etc. The data is then analyzed using qualitative analysis techniques. The results show that the Icelandic government issued an Equal Pay Certification policy which is the first policy in the world that requires companies and institutions to prove the application of an equal pay system through a strict audit process. The Act on Equal Status and Equal Rights Irrespective of Gender was also formulated to help improve Gender equality in various aspects. This policy has so far had a positive impact in reducing the Gender pay gap in the world of work